Peningkatan Keaktifan dan Hasil Belajar Ekonomi dengan Model Pembelajaran Kooperatif Tipe Make A Match Pada Peserta Didik Kelas X IPS 3 MAN 2 Bantul - Mas Indah Murdaningrum (Balai Diklat Keagamaan Semarang, 2021)
This study aims to increase the students' activeness and economic learning outcomes with the Make A Match Type Cooperative Learning Model at MAN 2 Bantul. The research subjects were 29 students of class X IPS 3 MAN 2 Bantul. Data collection techniques using observation and tests. The data analysis technique used descriptive quantitative. The results showed that learning using the Make A Match type cooperative model could increase the activeness and learning outcomes of students. This is evidenced by the increase in an economic learning activity in the first cycle, students who have a learning activity in the moderate category of at least 62.64%, in the second cycle it increases to 77.58%. The increase in student learning outcomes seen from the average class of cycle I to cycle II has increased. Students who have completed learning in the first cycle are 62.07% and increased in the second cycle by 86.21.